Particle reinforced carbon dioxide absorbent and preparation method thereof

Solid particles are prepared by the black powder leaching slag obtained in the retired ternary lithium-ion battery recycling process and added to the absorbent of alcohol amines to form a particle-enhanced carbon dioxide absorbent, which solves the problem of high energy consumption in the absorbent regeneration process in the prior art, and achieves efficient and low energy consumption separation of low concentration CO2.

CN119588113AActive Publication Date: 2025-03-11ZHEJIANG UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411591375.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-11
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In the existing carbon dioxide capture technology, high energy consumption in the absorbent regeneration process is a key and primary issue. It is necessary to find low-energy-consuming and high-efficiency absorbents to reduce CO2 emissions and carbon capture costs.

Method used

By calcining and ball milling the black powder leaching residue obtained in the retired ternary lithium-ion battery recovery process, solid particles are prepared and added to the absorbent of alcohol amines to form a particle-enhanced carbon dioxide absorbent. This method not only reduces the cost of absorbent and regeneration energy consumption, but also improves the absorption and desorption properties of CO2.

Benefits of technology

High-efficiency and low-energy-consuming separation of low-concentration CO2 is achieved, reducing the energy consumption of the absorbent desorption and reducing the cost of the absorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588113A_ABST
    Figure CN119588113A_ABST
Patent Text Reader

Abstract

The invention provides a particle reinforced carbon dioxide absorbent and a preparation method thereof. The total mass of the particle reinforced carbon dioxide absorbent is 100%, and the absorbent comprises 0.05%-0.3% of a solid phase and 99.7%-99.95% of a liquid phase. The preparation of the solid phase comprises the following steps: mechanically disassembling a retired ternary lithium ion battery to obtain an electrode material, namely black powder, roasting the black powder in a chain furnace, leaching the roasted black powder by using sulfuric acid, drying black powder leaching residues, and carrying out ball milling treatment after drying to finally obtain solid particles. The preparation method of the absorbent comprises the following steps: mixing solid particles, a chemical absorbent and water according to a certain proportion, and stirring and ultrasonically dispersing to form a dispersed and stable suspension. The particle-reinforced carbon dioxide absorbent provided by the invention has excellent absorption and desorption dynamic performance on low-concentration CO2, can reduce desorption energy consumption, and realizes high-efficiency and low-energy-consumption separation of CO2 in low-concentration CO2 mixed gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mixed gas separation and purification, and in particular to a particle-enhanced carbon dioxide absorbent and a preparation method thereof. Background Art

[0002] The continuous emission of carbon dioxide, which accounts for 60% of the total greenhouse gases, has led to global warming and is a challenge faced by all mankind. Therefore, reducing carbon dioxide emissions is the most effective means to control the greenhouse effect. Carbon dioxide capture, utilization and storage (hereinafter referred to as CCUS) technology is considered to be an effective way to achieve carbon dioxide emission reduction. The chemical absorption method based on organic amine absorbents has been widely used in post-combustion CO2 capture. For this technology, the high energy consumption of the absorbent regeneration process is the key and primary problem that needs to be solved. Therefore, finding a low-energy, high-efficiency absorbent is very important for reducing CO2 emissions and reducing carbon capture costs.

[0003] Nanoparticles have a significant strengthening effect on heat and mass transfer processes. In the field of CO2 chemical absorption, nanoparticles can promote gas-liquid mass transfer during CO2 absorption and desorption due to their size advantage. Compared with traditional CO2 absorbents, nanofluid absorbents prepared based on nanoparticles also have some special properties, such as high thermal stability and low vapor pressure, etc., so they have potential industrial application value in carbon dioxide chemical absorption. However, the preparation process of nanoparticles is complicated and costly, which is not conducive to the promotion of nanofluid absorbents. Some particles produced in the recycling process have a small particle size and have the potential for gas adsorption and enhanced mass transfer. Modifying these particles and dispersing them in the absorbent to form a stable suspension can also enhance CO2 absorption and desorption, achieve low desorption energy consumption and reduce the cost of the absorbent. Summary of the invention

[0004] Based on the above background, the purpose of the present invention is to provide a particle-enhanced carbon dioxide absorbent, which enhances the CO2 absorption and desorption performance and can reduce the desorption energy consumption of the CO2 absorbent at a low cost.

[0005] To achieve the above object, the present invention provides a method for preparing a particle-enhanced carbon dioxide absorbent as follows:

[0006] A particle-enhanced carbon dioxide absorbent, based on the total mass of the absorbent being 100%, the composition of the absorbent includes 0.05%-0.3% of a solid phase and 99.7%-99.95% of a liquid phase, wherein the solid phase is solid particles; based on the total mass of the liquid phase being 100%, the composition of the liquid phase includes 30%-60% of a chemical absorbent and 40%-70% of water; the chemical absorbent is one or a combination of two or more of alcohol amine substances.

[0007] Preferably, the solid particles are prepared by mechanically disassembling retired ternary lithium-ion batteries to obtain an electrode material mixture, namely black powder, calcining the black powder in a chain furnace at 500°C to 800°C, controlling the oxygen concentration in the calcining atmosphere to be lower than 0.3%, leaching the calcined black powder with sulfuric acid, drying the black powder leached residue, and then ball milling the leached residue to finally obtain solid particles. The solid particles are mainly composed of carbon and oxygen, as well as a small amount of nickel, cobalt, manganese and sulfur.

[0008] Preferably, the ball milling process is: the frequency is 10 Hz, and the duration is 5-30 min. More preferably, the ball milling process is: removing particles with larger particle sizes through a 500-mesh sieve, and ball milling for 15 minutes at a vibration frequency of 10 Hz.

[0009] Preferably, the solid particles contain, by weight percentage, 17%-18% oxygen, 3%-4% nickel, 1%-2% cobalt, 7%-8% manganese and 5%-6% sulfur, with the remainder being carbon.

[0010] Preferably, the added amount of the solid phase is 0.05%-0.2%.

[0011] Preferably, the black powder is calcined at a temperature of 600°C.

[0012] Preferably, the alcoholamine substance includes one or a combination of two or more of ethanolamine (MEA), diethanolamine (DEA), N-(2-hydroxyethyl)ethylenediamine (AEEA) and diethylaminoethanol (DEEA).

[0013] Preferably, based on the total mass of the absorbent as 100%, the composition of the absorbent includes 0.10% solid particles, 2.5 mol / L ethanolamine, 2.5 mol / L diethylaminoethanol, and the balance is water; or, 0.10% solid particles, 5 mol / L diethanolamine, and the balance is water.

[0014] A preparation method of the particle-enhanced carbon dioxide absorbent is specifically: solid and liquid raw materials are mixed in proportion, stirred, and ultrasonically dispersed to form a dispersed and stable suspension; the stirring rate is 100-200 rpm, and the stirring time is 3-4 hours; the ultrasonic temperature is controlled at 30-50°C, and the ultrasonic time is 10-15 minutes.

[0015] According to a specific embodiment of the present invention, the preparation method of the above-mentioned particle-enhanced carbon dioxide absorbent includes the following steps: mixing solid particles, chemical absorbent and water in proportion, controlling the rotation speed at 100-200 rpm, stirring for 3-4 hours, and then controlling the temperature at 30-50°C for ultrasonic dispersion for 10-15 minutes to make it a dispersed and stable suspension.

[0016] Compared with the existing absorbents, the present invention has the following advantages: the particle-enhanced carbon dioxide absorbent of the present invention is obtained by reusing the black powder leaching residue obtained in the recycling process of retired ternary lithium-ion batteries and adding it as solid particles, thereby enhancing the capture performance of the existing CO2 absorbent and reducing the cost and regeneration energy consumption of the absorbent; it has better absorption and desorption kinetics for low-concentration CO2, and can reduce the desorption energy consumption, thereby realizing efficient and low-energy separation of CO2 in low-concentration CO2 mixed gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0018] Figure 1 A device for evaluating the absorption and desorption performance of the CO2 absorbent in Examples 1 and 2 of the present invention;

[0019] Figure 2 This is a graph showing the change in absorption rate of the CO2 absorbent over time in Example 1 of the present invention;

[0020] Figure 3 This is a graph showing the change in the absorption load of the CO2 absorbent over time in Example 1 of the present invention;

[0021] Figure 4 This is a graph showing the change in desorption rate of the CO2 absorbent over time in Example 1 of the present invention;

[0022] Figure 5 This is a graph showing the change in desorption load of the CO2 absorbent over time in Example 1 of the present invention;

[0023] Figure 6 This is a graph showing the change in absorption load of the CO2 absorbent over time in Example 2 of the present invention;

[0024] Figure 7 This is a graph showing the change in desorption load of the CO2 absorbent over time in Example 2 of the present invention;

[0025] Figure 8The particle size distribution diagram of the CO2 absorbent solid particles after different ball milling times in the embodiment of the present invention;

[0026] Fig. 9 The specific surface area and pore volume of the CO2 absorbent solid particles after different ball milling times in the embodiment of the present invention;

[0027] Fig.10 is the contact angle of the solid particulate material;

[0028] Fig.11 The scanning electron microscope and energy spectrum diagram of the CO2 absorbent solid particles in Examples 1 and 2 of the present invention;

[0029] Fig.12 Element atomic ratio diagram of CO2 absorbent solid particles in Examples 1 and 2 of the present invention;

[0030] Fig.13 4 is a diagram showing the element mass ratio of the CO2 absorbent solid particles in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.

[0032] In the present invention, unless otherwise specified, all parts and percentages are weight units, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art. The components or equipment in the following embodiments, unless otherwise specified, are universal standard parts or components known to those skilled in the art, and their structures and principles can be learned by those skilled in the art from technical manuals or through conventional experimental methods.

[0033] The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following detailed description, for the convenience of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention.

[0034] The present invention provides a particle-enhanced carbon dioxide absorbent, which includes 0.05%-0.3% of a solid phase and 99.7%-99.95% of a liquid phase. The solid phase is solid particles; based on the total mass of the liquid phase being 100%, the composition of the liquid phase includes 30%-60% of a chemical absorbent and 40%-70% of water; the chemical absorbent is one or a combination of two or more alcohol amine substances.

[0035] In the carbon dioxide absorbent of the present invention, the liquid phase in the carbon dioxide absorbent includes a chemical absorbent and water, the chemical absorbent is mainly one or two of the alcohol amine substances, and the ratio of the solid phase to the liquid phase is controlled within a suitable range, which can improve the absorption and desorption performance of the absorbent.

[0036] The preparation method of the particle-enhanced carbon dioxide absorbent of the present invention comprises the following steps: mixing solid particles, chemical absorbent and water in proportion, controlling the rotation speed at 100-200 rpm, stirring for 3-4 hours, and then controlling the temperature at 30-50° C. for ultrasonic dispersion for 10-15 minutes to make it a dispersed and stable suspension.

[0037] The absorbent absorption performance testing method in the embodiment of the present invention is as follows: Figure 1 (a), comprising the following steps:

[0038] Take 25 mL of absorbent into a bubbling absorption bottle and place it in a constant temperature water bath at 40°C;

[0039] The gas flow rate was controlled by a mass flow controller at 250 mL / min, and a 15% CO2 + 85% N2 mixed gas was introduced into the bubbling absorption bottle to allow the absorbent to react fully;

[0040] The gas flow rate at the outlet is recorded using an electronic soap film flowmeter; when the gas flow rate at the outlet remains stable for 10 minutes, the solution reaches a state of absorption saturation and the CO2 absorption load reaches its maximum value;

[0041] The CO2 absorption rate of the absorbent can be calculated by the flow rate difference between the inlet and outlet gases. Then, the CO2 absorption load of the absorbent can be obtained by integrating the absorption rate with time. The calculation formula is:

[0042]

[0043] Among them, r a is the absorption rate of the absorbent (mmol / min); V in and V out are the gas flow rates at the inlet and outlet, respectively (mL / min); P and P0 are the atmospheric pressures under actual and standard conditions, respectively (kPa); T and T0 are the temperatures under actual and standard conditions, respectively (K); L a is the absorption load of the absorbent (mmol); t is the absorption saturation time (min).

[0044] The absorbent desorption performance test method in the embodiment of the present invention is as follows: Figure 1 (b) as shown, comprising the following steps: the CO2 desorption reactor is a three-necked glass flask, and a heat-collecting constant temperature magnetic stirring bath is used to provide a 120°C constant temperature oil bath environment for the reaction;

[0045] Before the experiment, heat the three-necked glass flask to the reaction temperature. When the temperature in the reactor is stable, quickly transfer 50 mL of saturated absorbent into the reactor, and try to use the reaction liquid that has just reacted to saturation to avoid premature desorption of the rich liquid. No additional gas purge is required during the reaction.

[0046] The bottom of the reactor uses a magnetic rotor to control the constant speed of about 200 rpm to stir and desorb the rich liquid to make the temperature uniform;

[0047] The desorption CO2 gas flow rate is measured and recorded by an electronic soap film flowmeter; when no gas flows out of the outlet for 10 minutes, the desorption reaction ends;

[0048] The CO2 desorption rate of the absorbent is calculated by the measured outlet gas flow rate, and then the desorption rate is integrated with time to obtain the desorption CO2 load. The calculation formula is:

[0049]

[0050] Where: L des is the desorption rate of the absorbent (mmol / min); V out are the CO2 gas flow rate at the outlet (mL / min); P and P0 are the atmospheric pressures (kPa) under actual and standard conditions; T and T0 are the temperatures (K) under actual and standard conditions; L des is the CO2 desorption amount of the absorbent rich liquid (mmol); t is the absorption saturation time (min).

[0051] Optimization of the solid particle preparation method of the embodiment

[0052] The solid phase of the present invention, i.e., the preparation steps of solid particles are as follows:

[0053] Mechanically dismantle retired ternary lithium-ion batteries to obtain a mixture of positive and negative electrode materials, namely black powder, which is roasted in a chain furnace at 600°C, and the oxygen concentration in the atmosphere is controlled to be less than 0.3%. The roasted black powder is leached with sulfuric acid, and the leached residue is dried and then ball-milled at a frequency of 10 Hz for 5-30 minutes to obtain solid particles at different ball-milling times. They are solid particles 1, solid particles 2, solid particles 3, and solid particles 4.

[0054] The battery black powder with larger particle size was removed through a 500-mesh sieve, and solid particles were prepared by the above-mentioned treatment method, wherein solid particle 1 was not treated in any way;

[0055] Solid particles 2 are particles of battery black powder after ball milling at a vibration frequency of 10 Hz for 5 minutes;

[0056] Solid particles 3 are particles of battery black powder after ball milling at a vibration frequency of 10 Hz for 15 minutes;

[0057] Solid particles 4 are particles of battery black powder after ball milling at a vibration frequency of 10 Hz for 30 minutes;

[0058] like Figure 8 As shown in the figure, the particle sizes of the four solid particles are mainly distributed between 488-660nm. Fig. 9 As shown, the specific surface area and pore volume of the solid particles increase with the increase of ball milling time. The specific surface area of ​​solid particle 4 is doubled compared with solid particle 1, and the pore volume is significantly increased, while compared with solid particle 3, the increase is smaller, and the impact of ball milling on the particles is reduced. Therefore, the preparation conditions of solid particle 3 are optimal.

[0059] Fig.10 The contact angle of the solid particle material is characterized. The solid particle material has good hydrophilicity, which is conducive to uniform dispersion in the liquid phase. Among them, the scanning electron microscope image of the solid particles is as follows Fig.11 As shown, the atomic ratio and weight ratio of the elements are Fig.12 and Fig.13 As shown. According to the SEM-EDS spectrum, the main component of the leached residue is carbon, accounting for 78.02% of the atom, which comes from the graphite of the negative electrode of the lithium-ion battery. A small amount of impurities such as manganese sulfate are attached to the surface, which is the residual positive electrode material after acid leaching. Fig.13 It can be seen that the obtained solid particles contain 17.85% oxygen, 3.29% nickel, 1.88% cobalt, 7.63% manganese and 5.2% sulfur, and the balance is carbon.

[0060] In the following examples, the prepared solid particles 3 are selected as the black powder leaching residue of ternary lithium-ion battery for testing.

[0061] Example 1

[0062] This embodiment provides a group of particle enhanced carbon dioxide absorbents, namely: absorbent 1, absorbent 2, absorbent 3, absorbent 4, absorbent 5;

[0063] The absorbent is prepared by the above-mentioned preparation method of the particle-enhanced carbon dioxide absorbent, wherein:

[0064] The composition of absorbent 1 is (5 mol / L ethanolamine + balance water);

[0065] The composition of absorbent 2 is (0.05% ternary lithium-ion battery black powder leaching residue + 5 mol / L ethanolamine + balance water);

[0066] The composition of absorbent 3 is (0.1% ternary lithium-ion battery black powder leaching residue + 5 mol / L ethanolamine + balance water);

[0067] The composition of absorbent 4 is (0.2% ternary lithium-ion battery black powder leaching residue + 5 mol / L ethanolamine + balance water);

[0068] The composition of absorbent 5 is (0.3% ternary lithium-ion battery black powder leaching residue + 5 mol / L ethanolamine + balance water);

[0069] The absorption rate and absorption load of each absorbent were tested using the above absorption device test method. The results are as follows: Figure 2 and Figure 3 shown. Figure 2 and Figure 3 In the figure, the horizontal axis is time, and the vertical axis is absorption rate and absorption load. As can be seen from the figure, compared with blank absorbent 1, adding a certain proportion of ternary lithium-ion battery black powder leaching residue helps to improve the absorption rate and absorption load of the absorbent. The absorption rates of absorbents 2, 3, and 4 are faster overall, while absorbent 5 has a lower absorption rate due to excessive solid particle concentration, which is lower than absorbent 1. After absorption saturation, the CO2 absorption load is shown in Table 1, among which the absorption loads of absorbents 2, 3, and 4 are all greater than that of blank absorbent 1, the absorption load of absorbent 5 is lower than that of absorbent 1, and the absorption load of absorbent 3 is the largest. Therefore, the solid particle formula concentration of absorbent 3 is optimal.

[0070] Table 1 Example 1 CO2 absorption load

[0071] Absorbent <![CDATA[CO2 absorption load (mmol)]]> Absorbent 1 66.53 Absorbent 2 68.24 Absorbent 3 69.99 Absorbent 4 68.36 Absorbent 5 61.75

[0072] The above desorption device test method was used to test the desorption rate and desorption load of each absorbent. The results are as follows: Figure 4 and Figure 5 shown. Figure 4 and Figure 5 In the figure, the horizontal axis is time, and the vertical axis is desorption rate and desorption load, respectively. It can be seen from the figure that compared with absorbent 1, the maximum desorption rate of absorbent 2, absorbent 3, and absorbent 4 is higher, while the desorption rate of absorbent V is slower. After the desorption is complete, the amount of desorbed CO2 is shown in Table 2, among which the amount of desorbed CO2 of absorbent 2, absorbent 3, and absorbent 4 is greater than that of absorbent 1, the amount of desorbed CO2 of absorbent 5 is lower than that of absorbent 1, and the amount of desorbed CO2 of absorbent 3 is the largest. Therefore, the solid particle formula concentration of absorbent 3 is optimal, which is 0.10% of the addition amount.

[0073] Table 2 Example 1 Desorption of CO2

[0074] Absorbent <![CDATA[Amount of desorbed CO2 (mmol)]]> Absorbent 1 56.94 Absorbent 2 57.90 Absorbent 3 61.27 Absorbent 4 57.45 Absorbent 5 54.93

[0075] Example 2

[0076] This embodiment provides a group of particle enhanced carbon dioxide absorbents, namely: absorbent 6, absorbent 7, absorbent 8, absorbent 9, absorbent 10, absorbent 11, absorbent 12, and absorbent 13.

[0077] The absorbent is prepared by the above-mentioned preparation method of the particle-enhanced carbon dioxide absorbent, wherein:

[0078] The composition of absorbent 6 is (5 mol / L diethanolamine + balance water);

[0079] The composition of absorbent 7 is (0.1% ternary lithium-ion battery black powder leaching residue + 5 mol / L diethanolamine + balance water);

[0080] The composition of absorbent 8 is (5 mol / L N-(2-hydroxyethyl)ethylenediamine + balance water);

[0081] The composition of absorbent 9 is (0.10% ternary lithium-ion battery black powder leaching residue + 5 mol / L N-(2-hydroxyethyl)ethylenediamine + balance water);

[0082] The composition of absorbent 10 is (5 mol / L diethylaminoethanol + balance water);

[0083] The composition of the absorbent 11 is (0.10% ternary lithium-ion battery black powder leaching residue + 5 mol / L diethylaminoethanol + balance water);

[0084] The composition of absorbent 12 is (2.5 mol / L ethanolamine + 2.5 mol / L diethylaminoethanol + balance water);

[0085] The composition of the absorbent 13 is (0.10% ternary lithium-ion battery black powder leaching residue + 2.5 mol / L ethanolamine + 2.5 mol / L diethylaminoethanol + balance water);

[0086] The absorption rate and absorption load of each absorbent were tested using the above absorption device test method. The results are as follows: Figure 6 shown. Figure 6 In the figure, the horizontal axis is time and the vertical axis is absorption load. It can be seen from the figure that absorbent 7, absorbent 9, absorbent 11 and absorbent 13 have faster absorption rates compared with absorbent 6, absorbent 8, absorbent 10 and absorbent 12 respectively. The CO2 absorption load after absorption saturation is shown in Table 3. The CO2 absorption load of absorbent 7, absorbent 9, absorbent 11 and absorbent 13 is greater than that of the comparative absorbent. Therefore, the addition of 0.10% solid particles has a certain enhancement effect on the absorption performance of different organic amine absorbents or mixed amine absorbents.

[0087] Table 3 Example 2 CO2 absorption load

[0088] Absorbent <![CDATA[CO2 absorption load (mmol)]]> Absorbent 6 62.36 Absorbent 7 64.14 Absorbent 8 108.91 Absorbent 9 115.00 Absorbent 10 71.22 Absorbent 11 74.13 Absorbent 12 30.32 Absorbent 13 32.92

[0089] The above desorption device test method was used to test the desorption rate and desorption load of each absorbent. The results are as follows: Figure 7 shown. Figure 7 In the figure, the horizontal axis is time and the vertical axis is desorption load. It can be seen from the figure that absorbent 7, absorbent 9, absorbent 11 and absorbent 13 have faster desorption rates compared with absorbent 6, absorbent 8, absorbent 10 and absorbent 12 respectively. The amount of CO2 desorbed by each absorbent after desorption is complete is shown in Table 3. The amount of CO2 desorbed by absorbent 7, absorbent 9, absorbent 11 and absorbent 13 is greater than that of the comparative absorbent. Therefore, the addition of 0.10% solid particles also has a certain enhancement effect on the desorption performance of different organic amine absorbents or mixed amine absorbents.

[0090] Table 4 Example 2 Desorption of CO2

[0091]

[0092]

[0093] According to the above test results, the formula of absorbent 7 and absorbent 13 has the best effect, has better absorption and desorption kinetics for low-concentration CO2, and can reduce the desorption energy consumption, thereby achieving efficient and low-energy separation of CO2 in low-concentration CO2 mixed gas.

[0094] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0095] The above is a detailed introduction to a particle-enhanced carbon dioxide absorbent and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A particle enhanced carbon dioxide absorbent, characterized in that: Based on the total mass of the absorbent being 100%, the absorbent comprises 0.05% to 0.3% of a solid phase and 99.7% to 99.95% of a liquid phase. The solid phase is solid particles; taking the total mass of the liquid phase as 100%, the composition of the liquid phase includes 30%-60% of chemical absorbent and 40%-70% of water; the chemical absorbent is one or a combination of two or more alcohol amine substances.

2. The particle-enhanced carbon dioxide absorbent according to claim 1, characterized in that: The preparation method of the solid particles is: mechanically dismantling retired ternary lithium-ion batteries to obtain an electrode material mixture, namely black powder, roasting the black powder at 500° C. to 800° C. in a chain furnace, controlling the oxygen concentration in the roasting atmosphere to be lower than 0.3%, leaching the roasted black powder with sulfuric acid, drying the black powder leached residue, and then ball milling the leached residue to finally obtain solid particles.

3. The particle-enhanced carbon dioxide absorbent according to claim 2, characterized in that: The ball milling process is: the frequency is 10 Hz, and the duration is 5-30 min.

4. The particle-enhanced carbon dioxide absorbent according to claim 2, characterized in that: The ball milling treatment is as follows: the particles with larger particle sizes are removed through a 500-mesh sieve, and the ball milling is performed at a vibration frequency of 10 Hz for 15 minutes.

5. The particle-enhanced carbon dioxide absorbent according to claim 1, characterized in that: The solid particles contain, by weight percentage, 17%-18% oxygen, 3%-4% nickel, 1%-2% cobalt, 7%-8% manganese and 5%-6% sulfur, with the remainder being carbon.

6. The particle-enhanced carbon dioxide absorbent according to claim 1, characterized in that: The added amount of the solid phase is 0.05%-0.2%.

7. The particle-enhanced carbon dioxide absorbent according to claim 2, characterized in that: The black powder calcining conditions are: calcining temperature 600°C.

8. The particle-enhanced carbon dioxide absorbent according to claim 3, characterized in that: The alcoholamine substances include one or a combination of two or more of ethanolamine (MEA), diethanolamine (DEA), N-(2-hydroxyethyl)ethylenediamine (AEEA) and diethylaminoethanol (DEEA).

9. The particle-enhanced carbon dioxide absorbent according to claim 1, characterized in that: Taking the total mass of the absorbent as 100%, the absorbent comprises 0.10% solid particles, 2.5 mol / L ethanolamine, 2.5 mol / L diethylaminoethanol, and the balance is water; or, 0.10% solid particles, 5 mol / L diethanolamine, and the balance is water.

10. A method for preparing the particle-enhanced carbon dioxide absorbent according to claim 1, characterized in that: The solid and liquid raw materials are mixed in proportion, stirred, and ultrasonically dispersed to form a dispersed and stable suspension; the stirring rate is 100-200rpm, and the stirring time is 3-4 hours; the ultrasonic temperature is controlled at 30-50°C, and the ultrasonic time is 10-15 minutes.

Citation Information

Patent Citations

  • Method for processing battery black powder and preparing regenerated graphite negative electrode and application thereof

    CN115882098A

  • Recycling method of waste lithium ion battery

    CN116053632A

  • Method for preparing carbon dioxide adsorbent, carbon dioxide adsorbent and application of carbon dioxide adsorbent

    CN116920788A

  • Lithium carbonate recovery method based on retired lithium ion battery

    CN117430142A

  • Carbon dioxide absorbents comprising nanoparticle

    KR101296512B1